Public Relations Utilization of AI Algorithms to Analyze Fan Sentiments toward Saudi Clubs on Social Media (The International Journal of Educational Sciences and Arts, 2025)
This study aimed to analyze the extent to which public relations in Saudi sports clubs employ artificial intelligence (AI) algorithms to understand fan sentiment on social media. Data was collected through a questionnaire targeting public relations practitioners in Saudi sports clubs, and the study adopted a descriptive-analytical approach. The study highlighted the importance of AI in providing precise insights into fan trends, aiding in the development of effective strategies to enhance the fan experience and interaction between clubs and their supporters. It also reviewed the theoretical framework, relevant previous studies, key concepts, and the methodological procedures employed in the research. The study was based on the Unified Theory of Acceptance and Use of Technology and was applied to public relations professionals in Saudi sports clubs across various divisions. The final sample consisted of 89 respondents out of 98, yielding a response rate of 91%. The study's main findings regarding audience sentiment analysis are that AI technologies have contributed to improving public relations strategies and enhancing the public image of sports clubs. Regarding public relations practitioners' awareness of the importance of AI, the study found that practitioners are highly aware of its importance, with the majority willing to adopt it in their daily tasks. Also, regarding enhancing audience engagement, the study demonstrated that sentiment analysis tools help clubs understand their fans' needs, which positively impacts engagement and management decisions.The study recommended the need to increase investments in AI technologies within sports clubs, develop digital infrastructure to enable the use of sentiment analysis more effectively, and establish clear mechanisms to address the challenges of confidentiality and security in audience data analysis. The study confirmed that the use of AI in public relations opens new horizons for improving performance and strengthening the relationship between clubs and their fans, making the adoption of these technologies a necessity to keep pace with digital developments in the sports field.
Keywords: Public Relations; Artificial Intelligence Algorithms; Sentiment Analysis; Fans; Saudi Clubs; Social Media